PELAKSANAAN UNDANG UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG UNDANG NOMOR 1 TAHUN 1974 DALAM MENURUNKAN ANGKA PERNIKAHAN ANAK DI BAWAH UMUR DI KABUPATEN LANGKAT (STUDI KASUS DI PENGADILAN AGAMA STABAT KELAS IB) - muhammad abidin; Milhan Milhan; Heri Firmansyah (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2021)
abstract  Implementation of Law of the Republic of Indonesia Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage in reducing the number of child marriages in Langkat Regency, the reality of implementing Law of the Republic of Indonesia Number 16 of 2019 in reducing child marriage rates Underage children in the Stabat Religious Court can still be said to have not been optimal in their implementation in reducing the number of underage marriages. The implications of this research include: there are still many people who do not understand so that the author through this thesis can provide knowledge to the public about the consequences after underage marriage and the importance of the ideal age in carrying out marriage so that the realization of the purpose of marriage itself is contained in the spirit of Article 1 Law of 1974 concerning Marriage. That is to create a happy eternal family according to God Almighty and allow the creation of a sakinah, mawaddah and rahmah family. Keywords: Implementation, Law No. 16 Year 2019, Lowering Marriage